Mapping street sounds in the nineteenth-century city: a listener's guide to social engineering*. Issue 2 (3rd July 2018) - Llano, Samuel
Abstract: Listening in the nineteenth-century city was regulated by mapping techniques that were specific to that context. Sound mapping did not consist only on locating sounds on a two-dimensional representation of physical space. It also relied on the use inscriptions, laws and discourse to make reality conform to a certain mental map, in which acoustic territories were delimited by concerns and anxieties with the support of economic and political power. Sound mapping technologies were at the service of those who control the narrative of how maps – broadly understood – were meant to be read. Sound control in the nineteenth century city was not subordinated to the supposed prevalence of the visual, but was rather dependent on psychological and legal mechanisms developed in reaction to smell and, related to this, in response to fears of contagion. These sentiments translated into experiments of social segregation such as the planned expansion of Madrid (1860). The appropriation and control of acoustic territories in the city was driven by an interest in protecting lifestyles and class interests. The contingency of the "sound" and "noise" categories made the distinction between them subject to a process of negotiation through which social and moral orthodoxies were established, and marginal groups were controlled or excluded.